2015
DOI: 10.1111/jan.12836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intervention with drinking chamomile tea on sleep quality and depression in sleep disturbed postnatal women: a randomized controlled trial

Abstract: Chamomile tea may be recommended to postpartum women as a supplementary approach to alleviating depression and sleep quality problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 33 publications
1
62
1
2
Order By: Relevance
“…Owing to the fact that chamomile is widely referred to as a sedative therapy and sleep helper, our study also highlights the significant improvement of sleep quality when using chamomile for 4 weeks as compared with placebo. The results were consistent after we excluded one study that reported sleep quality outcome using PSQS scale (Chang & Chen, ). These effects may be as a result of the presence of flavonoid apigenin, which can directly bind to the brain, specifically the benzodiazepine receptors and result in these tranquilizing effects (R Avallone, Zanoli, Corsi, Cannazza, & Baraldi, ; Srivastava et al, ).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Owing to the fact that chamomile is widely referred to as a sedative therapy and sleep helper, our study also highlights the significant improvement of sleep quality when using chamomile for 4 weeks as compared with placebo. The results were consistent after we excluded one study that reported sleep quality outcome using PSQS scale (Chang & Chen, ). These effects may be as a result of the presence of flavonoid apigenin, which can directly bind to the brain, specifically the benzodiazepine receptors and result in these tranquilizing effects (R Avallone, Zanoli, Corsi, Cannazza, & Baraldi, ; Srivastava et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…After 4 weeks from the administration of oral chamomile, there was a significant reduction in the PSQI and PSQS scales, indicating an improvement in the sleep quality of the studied patients (SMD = −0.73, 95% CI [−1.23, −0.23], P = 0.0042; Figure b) and with high heterogeneity between the studies ( p < 0.01, I 2 = 85%). However, omitting one study did not change either significant reduction or the heterogeneity (Chang & Chen, ; Figure ). Additionally, we have performed a sensitivity analysis based on the type of chamomile (by excluding the studies that did not report the type of chamomile), country (by analyzing Iranian studies only), the scale of measurement (by analyzing studies that used PSQI only), and design (by analyzing RCTs only and excluding the quasi trial) and compare it with the main analysis that included all the six studies assessing sleep quality.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Chamomile tea was recommended to postpartum women as a supplementary approach to alleviate depression and sleep quality problems limited to the immediate term 18 . Aroma therapy with Citrus arantium on post caesarean pain and vital signs among 80 women, reported that the use of Citrus arantium was effective in reducing pain after caesarean section 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the hypnotic agents often prescribed for hospital patients may not be advisable for antepartum patients due to potential adverse effects on the fetus. Although relatively few behavioral interventions are available to pregnant women, studies have tested exercise, 13 mindful yoga, 14 guided imagery, 15 massage, 16,17 and drinking herbal tea 18,19 to facilitate relaxation to improve sleep during pregnancy. No studies were found that tested these types of interventions with hospitalized antepartum patients.…”
Section: Introductionmentioning
confidence: 99%